Sosialisasi Perkembangan Peserta Didik tentang Perkembangan Emosional dan Moral di RT 49 Sepinggan - Rahayu Sri Waskitoningtyas; Ryan Angga Pratama; Kiftian Hady Prasetya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
The purpose of this service is to find out how students develop emotionally and how students develop morally. This service is located in Bukit Anugerah Indah Housing Estate, RT 49, Sepinggan Village, Balikpapan City, East Kalimantan Province. The population of this service is the residents of Bukit Anugerah Indah Housing by taking research subjects from parents who have elementary school children. Data collection methods in the form of interviews and documentation. The data analysis technique in this service uses source triangulation, namely interviews with 3 mothers. It was found that the development of children varies depending on the age of the child, emotional development also affects what they think, emotions also describe what a person thinks. The more mature a person, the emotional level will rarely occur unlike in children which often happens. While moral development is very influential on a person's character, if someone wants to be respected, he must have good moral qualities, in school it is very good to be taught moral traits, to educate children to be better. In everyday life, it is also very necessary to teach children moral character, so that empathy, honesty, truth, and chastity will grow. Moral nature makes a person able to socialize with people.